A Simplified Approach for Evaluating the Flexural Response of Concrete Beams Reinforced With FRP Bars - Sun, Rui; Perera, Ricardo; Gu, Jintao; Wang, Yi (Frontiers in Materials, 2021)
This paper is proposed for modelling concrete beams reinforced with fiber reinforced polymer (FRP) bars in a simplified way. In order to appropriately model the FRP-reinforced concrete beams the stiffness matrix is developed in the frequency domain using fast Fourier Transform. Numerical results with the proposed spectral model for the load-displacement response and the shear stress distribution between FRP reinforcement and surrounding concrete are obtained for beams statically tested. Tens of elements are deployed in this work due to the simplicity of the proposed model. Using the same spectral model the natural frequency and mode shapes are evaluated since the frequency-dependent stiffness matrix enables it to apply for dynamic study, e.g. modal analysis. The feasibility of the proposed numerical approach for performing dynamic analysis especially for high frequency excitations in an efficient way makes it a promising tool for use in the field of structural health monitoring according to the changes in dynamic characteristics.